Tingkat Serangan Larva Spodoptera frugiperda terhadap Tanaman Jagung sebagai Tanaman Inang - Agustin, Meri; Lestari, Ria; Hesti, Hesti; Mahani, Siti; Maharani, Ester; Qoyyimul Amri, Muhammad (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Agustin M, Lestari R, Hesti H, Mahani S, Maharani E, Amri MQ. 2021. Attack rate of spodoptera frugiperda larvae on maize as hosts crop. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang, 20 Oktober 2021. pp. 763-770. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Spodoptera frugiperda or commonly known as armyworm is an invasive pest on maize. This pest has a characteristic Y shape on the anterior. The eggs are green and turn light brown when they hatch. S. frugiperda caused damage to all stages of maize, starting from vegetative phase to generative phase. Maize damage caused by S. frugiperda larvae can cause great losses for farmers, S. frugiperda larvae attacks can controlled with several techniques, preventive control is one of it. The following study aims to determine which larval instars are the most voracious, causing significant losses in maize cultivation. The research method is carried out by conducting a literature study and observation. Late larvae instar are thought to be the cause of the most significant damage to maize crops. Observations of S. frugipeda instars were carried out in a maize plantation area in North Indralaya District. Various instars of S. frugiperda were found in one field was observe. The majority are late instar larvae. While in 5th instar larvae the percentage of damage caused was 16,3% of the total foliage. In 6th instar larvae the level of damage caused is very large, reaching 77,2%. So it can be concluded that the larvae that cause the most damage are late instar larvae, namely 6th instar larvae.